Articular Cartilage Lesions of the Patellofemoral Joint in Dogs With Naturally Occurring Cranial Cruciate Ligament Disease. Issue 3 (29th January 2014) - Agnello, Kimberly A.; Holsworth, Ian G.; Caceres, Ana Vanessa; Brown, Dorothy Cimino; Runge, Jeffery; Schlicksup, Michael; Hayashi, Kei
<x xml:space="preserve">Abstract</x> Objective To evaluate frequency, severity, and location of patellofemoral (PF) osteoarthritis (OA) in dogs with naturally occurring cranial cruciate ligament (CCL) disease. Study Design Cross‐sectional observational study. Animals Dogs (n = 40; stifles, 44). Methods Stifle arthroscopic video recordings and radiographs were performed. Cartilage pathology was scored at 3 locations (proximal, middle, distal) in the trochlear groove and patella. A radiographic osteoarthrosis and synovial pathology score were assigned. A Kruskal–Wallis test was used to determine if lesion severity varied by site, synovitis, and osteoarthrosis, and the Dunn's test was used for pairwise comparisons. The variability of body weight was evaluated using 1 way ANOVA; P < .05 was considered significant. Results Cartilage pathology and synovitis was identified in all PF joints. The proximal aspect of the trochlear groove had significantly higher cartilage scores than the middle and distal sites and the middle groove site was significantly higher than the distal site. The distal aspect of the patella had significantly greater scores than the middle and proximal patellar locations. Higher synovitis scores were associated with increased cartilage scores. Cartilage scores were significantly greater in stifles with higher radiographic osteophytosis, tibial sclerosis, and patellar enthesiophytosis scores. Higher body weights were significantly associated with greater synovial and radiographic scores. Conclusions Dogs with CCL disease have a high incidence of PF cartilage pathology and the severity of cartilage lesions varies depending on location within the joint.